Effect of Interfacial Layers on the Device Lifetime of Perovskite Solar Cells. Issue 8 (10th May 2020) - Lim, Kyung‐Geun; Ji, Su Geun; Kim, Jin Young; Lee, Tae‐Woo
Abstract: Organic–inorganic hybrid perovskites have excellent optical and electronic properties; exploitation of these traits has increased the power conversion efficiency of perovskite photovoltaics (PePVs) to 25.2%. However, perovskites are chemically unstable, and this deficit has critically impeded their commercialization. Device degradation occurs at the interfaces of PePVs with multiple degradation mechanisms: decomposition of organic cations in perovskites; generation of inorganic byproducts in perovskites; superoxide or trap sites at the interface of the charge‐transport layer; excess charge carriers in perovskites; interfacial migration between perovskites and electrodes. This review considers the critical functions of the interfacial materials to overcome the various degradation at the interfaces of the PePVs. The working mechanisms stabilizing the interface of PePVs are categorized: passivation from atmosphere; inactivation of defect states; migration‐blocking. Then, the outstanding interfacial layers made of organic materials (defect passivation, physical robustness, and chemical inactivation) and inorganic materials (chemically passivating metal oxide, physically passivating metal oxide, and low‐temperature processed inorganic materials) are reviewed according to the stabilizing mechanisms. In addition, the influences of inorganic interconnecting layers in tandem PePVs are reviewed, with respect of various effects of interfacial buffer materials at the interface with perovskites. Abstract : This study considers the critical functions of the interfacial layer in overcoming the various degradations processed at the interfaces of organic–inorganic hybrid perovskites photovoltaics (PePVs). The mechanisms can also be categorized according to the cause of the degradation. The stabilizing processes that attenuate the corresponding degrading process are studied with respect to organic or inorganic interfacial materials in PePVs.